Blast and fragmentation loading indicative of a VBIED surrogate for structural panel response analysis. (April 2019) - Mellen, Phillip; Shanahan, Christine; Bennett, Terry
Highlights: Bare blast and Vehicle Bourne IED surrogate produced similar pressure profiles. Pressure histories found to be highly consistent across tests. Minor clearing effects observed in reflected pressures across panels. Fragment distributions and velocities recorded for Vehicle Bourne IED surrogate. Abstract: This paper presents the results of an experimental investigation that was conducted at the Australian Department of Defence, Port Wakefield Proof and Experimental Establishment, in South Australia. The tests were undertaken to quantify the blast and fragmentation loads produced by both bare charges and a VBIED surrogate. The VBIED surrogate was designed to produce fragmentation indicative of a Vehicle Bourne Improvised Explosive Device and, in doing so, capture some of the properties of a device of this type that are significantly different to cased charges and conventional munitions. Incident pressures were recorded at 3, 4, and 5 m from the charge and reflected pressures were recorded at 3 m and across a 1.2 × 1.2 m flat panel to capture clearing effects of pressure history. The average velocity and distribution of fragment impacts were recorded for a panel of the same size.